Enhancing Green Economic Circular Ecosystem Growth through AI-Based Waste Management Gamification - Parimita, Widya; Monoarfa, Terrylina Arvinta; Rahmi, Rahmi; Wibowo, Setyo Ferry; Musyaffi, Ayatulloh Michael (International Review of Management and Marketing, 2024)
The research emphasizes the critical role of technology in advancing the sustainable development of micro, small, and medium enterprises (MSMEs) while highlighting the importance of leadership within green organizations for effective implementation of green economy principles. This study seeks to deepen understanding of how green behaviours contribute to the sustainability of enterprises. Indonesia’s National Waste Management Information System highlights the urgency of this research, revealing that the country generates millions of tons of inadequately managed waste, leading to significant environmental challenges. To address this, the study focuses on mapping the needs of MSMEs to foster a green economic circular ecosystem. The researchers conducted in-depth interviews with stakeholders and focus group discussions with MSMEs already involved in waste management. Data were collected through online surveys and interviews, followed by content analysis to understand MSMEs’ green behaviors and sentiments. The findings indicate a strong demand for green programs that encourage environmentally friendly behaviors through gamification, such as waste banks that provide economic benefits to MSMEs. This study also contributes to the sustainable development goals by integrating community involvement in value co-creation, raising public awareness, and increasing income through waste management initiatives.